PENGARUH KEADILAN DISTRIBUTIF KARIR DAN KEADILAN PROSEDURAL KARIR TERHADAP PERILAKU RETALIASI KARYAWAN SWASTA DI DAERAH ISTIMEWA YOGYAKARTA (DIY) DENGAN KEPUASAN KARIR SEBAGAI VARIABEL PEMEDIASIAN - Majang Palup; Heru Kurnianto Tjahjono; Rafika Nuri (Universitas Paramadina, 2014)
AbstractThis research has two purposes. The first was to conduct furthertesting of the influence of distributive and procedural justice on careersatisfaction and workplace retaliation behavior. The second was to testwhether the relationship between distributive and procedural justice to theretaliation behavior mediated by career satisfaction.The data analysistechnique used in this study was SEM (Structural Equation Modeling) whichwas operated through the program AMOS (Analysis of Moment Structure).Data collection techniques used in this research was questionnaires. Thepopulation of this reaserch was private employees within Daerah IstemewaYogyakarta (DIY) and the samples were taken using convenience samplingtechnique. The number of the sample were 165 employees. The resultsindicated that career distributive and procedural justice are strong predictorto explain career satisfaction. Then career satisfaction were negativepredictor to explain retaliation behavior. This finding explained that careersatisfaction were mediation variable to explain the influence of distributivejustice to retaliation behavior. Beside that, career satisfaction wereimportant mediator to explained the influence of procedural justice toretaliation behavior. Both of career distributive and procedural justice hasno significant effect to predict retaliation behavior directly.